How Does Green Credit Promote Carbon Reduction? A Mediated Model - Lyu, Bai; Da, JingYi; Ostic, Dragana; Yu, HuaChen (Frontiers in Environmental Science, 2022)
Using China’s provincial panel data from 2006 to 2016, this paper develops a dynamic panel data model to investigate the impact and mechanism of green credit on carbon emissions at the national and regional levels. According to the findings, green credit significantly reduces carbon emissions, with the eastern region having the greatest reduction effect. Green credit, with the exception of the western region, has a strong positive impact on disruptive low-carbon innovation. When green credit is combined with disruptive low-carbon innovation, both can significantly reduce carbon emissions; however, the green credit impact diminishes. It can be concluded that disruptive low-carbon innovation has a mediation effect on green credit’s contribution to carbon emission reduction. As a result, China should broaden the scope of green credit, concentrate on providing high-quality low-carbon patented technology to science and technology enterprises, and alleviate their financing constraints. Furthermore, these enterprises should increase their output of disruptive low-carbon innovation while lowering carbon emissions through technological innovation.